Kritik Komunikasi Kampanye Publik pada Kampanye Stunting Dinas Kesehatan Kulon Progo Tahun 2018 - Ahmad Syafi'i Lubis (Universitas Gadjah Mada, 2022)
Nowadays the issue of children, food and nutrition because cases of malnutrition are still high. Indonesia is still a country with children with